2016
DOI: 10.1007/978-3-319-30671-1_22
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between User Perception and User Behaviour in Interactive Information Retrieval Evaluation

Abstract: Measures of user behaviour and user perception have been used to evaluate interactive information retrieval systems. However, there have been few efforts taken to understand the relationship between these two. In this paper, we investigated both using user actions from log files, and the results of the User Engagement Scale, both of which came from a study of people interacting with a novel interface to an image collection, but with a non-purposeful task. Our results suggest that selected behavioural actions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
(39 reference statements)
0
4
1
Order By: Relevance
“…Another interesting study, which was found to be aligned with our present research outcome, also proved that enjoyment was more significant than perceived ease of use and perceived usefulness when predicting technology acceptance among a group of teachers (Chen et al., 2012; Teo and Noyes, 2011). Lastly, the obtained result for user perception also found to be contradicted studies that demonstrated a positive and moderate relationship between user perception and user behavior (Zhuang et al., 2016). The rejection of H3, H4 and H5 may signify a shift in thinking paradigm among adolescents and young adults who are adept and savvy with digital technologies (Gan and Balakrishnan, 2017, 2018).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Another interesting study, which was found to be aligned with our present research outcome, also proved that enjoyment was more significant than perceived ease of use and perceived usefulness when predicting technology acceptance among a group of teachers (Chen et al., 2012; Teo and Noyes, 2011). Lastly, the obtained result for user perception also found to be contradicted studies that demonstrated a positive and moderate relationship between user perception and user behavior (Zhuang et al., 2016). The rejection of H3, H4 and H5 may signify a shift in thinking paradigm among adolescents and young adults who are adept and savvy with digital technologies (Gan and Balakrishnan, 2017, 2018).…”
Section: Discussioncontrasting
confidence: 55%
“…Lau (2011) investigated user perceptions for the adoption of Web 2.0 tools among hospital-based nurses and concluded that the identified behavioural perceptions are crucial to understand the adoption intention of Web 2.0 for knowledge sharing, learning, social interaction, and the production of collective intelligence. User perception is often associated with measures of perceived usability (Zhuang et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The UTAUT model focuses on user perception of the technology [91], including perceived usefulness and ease of use, perceived enjoyment [99], and satisfaction [16]. [103]. Studies discuss user perception in terms of theories of "technology acceptance" [43].…”
Section: Students' Use and Perception Of Online Learningmentioning
confidence: 99%
“…Moreover, after analysing the processed tweets, it is apparent that Twitter is now being used as a medium to express commuters’ grievances, with a preference for an instantaneous reaction rather than perception from the commuters’ end. However, user perception, defined as the degree of perceived usability of the service provided (Zhuang et al, 2016 ), would assist in analysing the perceived service quality of the Delhi metro. This will be accomplished through efforts by the DMRC and the Delhi metro’s social media management agency to advance the use of Twitter and nudge commuters to share their experiences with the service offered by making Twitter a forum for commuter interaction or engagement.…”
Section: Discussionmentioning
confidence: 99%